2008
DOI: 10.1080/10942910701584260
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Composition and Antioxidant Activities of Grape Seed Extract

Abstract: Grape seed extracts (GSEs,) obtained from Italian and Rhine Rieslings, were examined for polyphenolic composition and antioxidant activities using HPLC and ESR spectrometry. The seed extraction was carried out with ethyl acetate and ethanol. The contents of polyphenols, flavan-3-ols and antioxidant activities were found to be higher in ethyl acetate than in ethanolic extracts. IC 50 values were 0.1045 mg/mL and 0.0599 mg/mL for the stable DPPH radical in ethanolic and ethyl acetate extracts, respectively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
80
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 30 publications
9
80
2
Order By: Relevance
“…The results obtained were in agreement with work of other researchers. [7,[39][40][41][42][43][44]50] A high and significant correlation was observed between total anthocyanins and total phenolics (r = 0.88, p < 0.0001), while no significant correlation was found between total anthocyanins and TPC, similar to previous reports. [11,45] These results may be due to other un-quantified phenolics or vitamins, synergism among these compounds, major phenolics affecting the expected correlation between phenolics, and antioxidant activities.…”
Section: Total Phenolic Content Antioxidant Capacity and Phenolic Csupporting
confidence: 91%
See 1 more Smart Citation
“…The results obtained were in agreement with work of other researchers. [7,[39][40][41][42][43][44]50] A high and significant correlation was observed between total anthocyanins and total phenolics (r = 0.88, p < 0.0001), while no significant correlation was found between total anthocyanins and TPC, similar to previous reports. [11,45] These results may be due to other un-quantified phenolics or vitamins, synergism among these compounds, major phenolics affecting the expected correlation between phenolics, and antioxidant activities.…”
Section: Total Phenolic Content Antioxidant Capacity and Phenolic Csupporting
confidence: 91%
“…[49] High variability of antioxidant activity, among the different genotypes, clearly shows the potential value of certain new cultivars and advanced lines and, their possible use in breeding programs to develop new strawberry cultivars with higher amounts of antioxidant compounds. [50] Therefore, it would be of interest to explore further the relation between physical and chemical characteristics and, use it for selecting advanced strawberry lines in a breeding program.…”
Section: Resultsmentioning
confidence: 99%
“…[28] Several studies have revealed a positive correlation between the content of phenolic compounds and the antioxidant activity in plants. [16,29,30] In this experiment, it was tried to establish if there was a correlation between antioxidant activity of Allium L. plants processed under acidic conditions and content of phenols, sugars, thiosulfinates or thiols.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that food such as fruit, vegetable and seeds contain a significant amount of natural antioxidant components including phenolics (Mandic et al, 2008;Katalinic et al, 2004). Studies reported that there is a negative correlation found between dietary intake phenolics and coronary heart diseases, stroke and cancer (Sun et al, 2002).…”
Section: Introductionmentioning
confidence: 99%